A SATISFACTION OF OUTPATIENTS TOWARDS HEALTH SERVICE QUALITY AT BANJARMASIN SIAGA SPECIAL SURGICAL HOSPITAL: A SATISFACTION OF OUTPATIENTS TOWARDS HEALTH SERVICE QUALITY AT BANJARMASIN SIAGA SPECIAL SURGICAL HOSPITAL - Diaty, Rima; Purwanti, Sri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2024)
There is a relationship between responsiveness and tangible factors with outpatient satisfaction at Banjarmasin Siaga Special Surgical Hospital. However, there is no relationship between reliability, assurance, and empathy with outpatient satisfaction at Banjarmasin Siaga Special Surgical Hospital. Keywords: Patient satisfaction, outpatient care, service quality, hospital